2008
DOI: 10.1089/cbr.2008.0462
|View full text |Cite
|
Sign up to set email alerts
|

Protein- and DNA-Based Active Immunotherapy Targeting Interleukin-13 Receptor Alpha2

Abstract: High-grade astrocytoma (HGA) is an invariably fatal malignancy with a mean survival of 14 months de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…An in vitro cell uptake assay was performed on G48 human glioblastoma cells with and without unlabeled Pep-1L as blocking agent to demonstrate the specificity and binding efficiency of [ 64 Cu]Pep-1L. Previously, we reported that this cell line contains about 4,000,000 IL13RA2 binding sites [ 13 , 20 , 26 , 33 ]. [ 64 Cu]Pep-1L bound these IL13RA2-expressing cells, which was significantly inhibited by binding site blockade with unlabeled Pep-1L (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro cell uptake assay was performed on G48 human glioblastoma cells with and without unlabeled Pep-1L as blocking agent to demonstrate the specificity and binding efficiency of [ 64 Cu]Pep-1L. Previously, we reported that this cell line contains about 4,000,000 IL13RA2 binding sites [ 13 , 20 , 26 , 33 ]. [ 64 Cu]Pep-1L bound these IL13RA2-expressing cells, which was significantly inhibited by binding site blockade with unlabeled Pep-1L (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to brain cancer, IL13RA2 has also been reported to be highly expressed in other deadly malignancies, including melanoma, head and neck, ovarian and pancreatic cancers [ 22 24 ]. We and others have designed and developed a number of molecular targeted therapies based on IL13 and its derivatives that have shown their efficacy in preclinical models of various cancers [ 13 , 19 , 20 , 25 – 29 ]. In fact, our targeted IL13-based agents were recently used as targeting ligand in chimeric antigen receptor (CAR)-engineered T cells that are in clinical trials [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-13RA2 is highly overexpressed in GBM, with up to 30,000 binding sites per cultured GBM cells [ 61 ]. The GBM cell line G48a expresses about 4,000,000 binding sites for IL-13RA2 per cell [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. IL-13 binds to IL-13 receptor A1 (IL-13RA1), forms a more stable heterodimer with IL-4 receptor A (IL-4RA), and then activates downstream signaling pathways [ 62 , 74 , 81 ].…”
Section: Interleukin 13 Receptor Alpha 2 (Il-13ra2) In Glioma Treamentioning
confidence: 99%
“…Expression of IL-13RA2 and EphA2 is partially overlapping; hence, the combined overexpression is ~90% in patients with GBM (31). IL-13RA2 and EphA2 are targets for multiple therapeutic approaches currently in the clinic or under preclinical evaluation (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). The first generation of an IL-13-based cytotoxin produced in our laboratory, which nonspecifically targeted IL-13RA2, demonstrated clinical efficacy in patients with recurrent GBM (13,(53)(54)(55).…”
Section: Targeted Cytotoxic Therapy Of Gbmmentioning
confidence: 99%